The effects of machiavellian, equity sensitivity, and ethical sensitivity on the accounting students’ ethical perceptions in perceiving the accountants’ ethics - Irodatun Nadilla; Dodik Juliardi (Universitas Negeri Malang, 2021)
This study aims to examine the effect of Machiavellian, equity sensitivity, ethical sensitivity on the ethical perceptions of accounting students in perceiving the ethical behavior of accountants. The sampling method that used is proportional sampling. The participants of this study are S1/ D4 students from accounting study program in the level of 2016 at the State Universities (PTN) and the Private Universities (PTS) accredited A in Malang. The samples of this study were 381 accounting students from eight universities. The data analysis that used in this study is multiple linear regression. The results showed that Machiavellian had a positive effect on the accounting students' ethical perceptions of the accountant's ethical behavior, equity sensitivity had no effect on the accounting students' perceptions of the accountant's ethical behavior, and ethical sensitivity had a positive effect on the accounting students' ethical perceptions of the accountant's ethical behavior.